Phonological Interference of Mother Tongue on English Sound Production: A Contrastive Study Based on A Literature Review - Zulfitri Zulfitri; Deslinawati Panjaitan; Nilna Muhlihah Iqbal; Nuraisyah Nuraisyah; Abdul Manan Pane (STKIP Taman Siswa Bima, 2026)
Mastery of English as an international language requires proper sound production skills, but speakers from a variety of linguistic backgrounds often face systematic obstacles due to the influence of their first language sound system. This study aims to map the English sounds that are most susceptible to distortion by first language (L1), analyze these patterns of interference in a contrastive manner, and identify linguistic factors that determine their severity. The method used is library research with a qualitative approach, sourced from journal articles, books, and proceedings published in 2021–2025 which are searched through Google Scholar, ERIC, and DOAJ. Data analysis follows the stages of reduction, display, and verification. The results of the study showed that the dental fricative sounds /θ/ and /ð/, monophthongic vowel pairs, and complex consonant groups were the most susceptible segments to interference. The pattern of sound substitution is systematic and can be predicted through the framework of contrastive analysis. The severity of interference is determined by the typological distance between languages, the level of proficiency of the speaker, nonverbal intelligence, and the complexity of cross-lexical similarities. These findings are expected to be a foundation for teachers in designing more contextual and effective phonetic learning.